Critical Illness-Related Corticosteroid Insufficiency (CIRCI): A Narrative Review from a Multispecialty Task Force of the Society of Critical Care Medicine (SCCM) and the European Society of Intensive Care Medicine (ESICM). Issue 12 (December 2017) - Annane, Djillali; Pastores, Stephen M.; Arlt, Wiebke; Balk, Robert A.; Beishuizen, Albertus; Briegel, Josef; Carcillo, Joseph; Christ-Crain, Mirjam; Cooper, Mark S.; Marik, Paul E.; Meduri, Gianfranco Umberto; Olsen, Keith M.; et al.
Abstract : Objective: To provide a narrative review of the latest concepts and understanding of the pathophysiology of critical illness-related corticosteroid insufficiency (CIRCI). Participants: A multi-specialty task force of international experts in critical care medicine and endocrinology and members of the Society of Critical Care Medicine and the European Society of Intensive Care Medicine. Data Sources: Medline, Database of Abstracts of Reviews of Effects (DARE), Cochrane Central Register of Controlled Trials (CENTRAL) and the Cochrane Database of Systematic Reviews. Results: Three major pathophysiologic events were considered to constitute CIRCI: dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, altered cortisol metabolism, and tissue resistance to glucocorticoids. The dysregulation of the HPA axis is complex, involving multidirectional crosstalk between the CRH/ACTH pathways, autonomic nervous system, vasopressinergic system, and immune system. Recent studies have demonstrated that plasma clearance of cortisol is markedly reduced during critical illness, explained by suppressed expression and activity of the primary cortisol-metabolizing enzymes in the liver and kidney. Despite the elevated cortisol levels during critical illness, tissue resistance to glucocorticoids is believed to occur due to insufficient glucocorticoid alpha-mediated anti-inflammatory activity. Conclusions: Novel insights into the pathophysiology of CIRCI add to the limitations of the current diagnostic tools to identify at-risk patients and may also impact how corticosteroids are used in patients with CIRCI.